Estudio comparativo del uso progresivo de la fuerza en las legislaciones de los países de la Comunidad Andina, en el contexto de las manifestaciones de octubre de 2019 en el Ecuador y la violación del derecho a la vida y la integridad personal. - Saraguro Jaramillo, Santiago Paúl (2023)
The purpose of this research is to analyze, verify and demonstrate, from a comparative point of view, how the regulations related to the progressive use of force in Ecuador are ineffective, not very relevant and do not allow it to be a tool for good practice on the part of the public force, Contrary to what happens in other countries of the continent that have taken this problem with more importance and worked on different bills with the objective of delineating and establishing effective mechanisms of action according to the conditions and the level of resistance in different scenarios, as long as respect for human rights prevails and does not involve the violation of human rights. The progressive use of force by any element of the public force is undoubtedly linked to Human Rights, and the State is responsible for assuming such responsibility in the face of any type of violation, which is exercised through the various mechanisms that serve to maintain public order; Since it is unable to comply with this obligation, it is decided to create a competent and comprehensive public security system that complies with the guidelines established in both national and supranational regulations, which will guarantee the full protection of personal integrity, whether of the elements belonging to the public force or of the persons to whom the mechanisms of action and control are applied. To guarantee the faithful fulfillment of the rights recognized constitutionally and within international instruments, is an obligation of the State, in this sense it is not possible to expose or sacrifice the protection of these rights in order to maintain public safety; This is why, when delegating this mission to police officers or law enforcement agents, the guidelines created to comply with this precept must be strictly followed, adapting a mechanism that tends to create a life in society free of violence, in which the mission of this law enforcement institution is aimed at protecting citizens and is not a mere element of protection of the State, only in the face of social protest. In recent times there have been events of great national commotion with which the excessive use of force and mishandling of the tools provided by members of the National Police of Ecuador and the Armed Forces is repeatedly evidenced, the delegation of this function to law enforcement officers, without the creation of a legal system that corresponds to the different social realities and provides for the strict observance of human rights, has created a gap that leads to the excessive use of force. 5 The Ecuadorian State through the legislature has granted police officers the legal protection to act within the fulfillment of their constitutional mission; through the reform of the Organic Integral Penal Code (COIP), where a new cause of exclusion of unlawfulness is considered to the fulfillment of the legal duty of the police officer; once the State considers the role of guarantor of rights and responsible for providing a public security system that protects the integrity of the individual.